Comparative analysis of clinical outcome and quality of life between amputations and combined bone and flap reconstructions at the lower leg. Issue 22 (23rd October 2022) - Behr, Björn; Lotzien, Sebastian; Flecke, Marcel; Wallner, Christoph; Wagner, J. Maximillian; Dadras, Mehran; Daigeler, Adrien; Schildhauer, Thomas A.; Lehnhardt, Marcus; Geßmann, Jan
Abstract: Purpose: At the lower leg, soft tissue defects with exposed bones, tendons, or hardware require flap coverage. In this retrospective study, we analyzed combined bone and soft tissue reconstructions compared to amputations of the lower leg in a civilian setting. Materials and methods: Patients who underwent combined bone and flap reconstruction (LR) or amputation (LA) of the lower leg were eligible for the study. Bone conditions included fractures and bony defects due to posttraumatic osteomyelitis and non-union. Besides the analysis of the medical history, the study included clinical examination including extremity functional scale (LEFS) and SF-36-questionnaire. Results: LEFS score was significantly higher in the LR group compared to the LA group. Importantly, 42% in the LR group as opposed to 80% in the LA group could not return to their occupation. Mean hospitalization was 119 in the LR and 49 days in the LA group. SF-36 body item scores were significantly higher in the LR group as compared to LA. Conclusions: Patients undergoing complex extremity reconstructions, including flap transfer to the lower leg have better functionality and higher quality of life than amputated patients. These data emphasize the advantages of these procedures and justify reconstructive efforts for limb salvage. Level of Evidence III. Implications for Rehabilitation: Amputation and combined bone and flap reconstruction in severe injuries of the lower leg can imply functional disabilities even after successful treatment. Albeit longer hospitalizations, patients with complex reconstructions showed better functional outcomes and had a higher quality of life. Limb salvage showed better functional outcomes and a higher rate in reintegration to work as compared to limb amputation. These data emphasize the importance of complex bone and soft tissue reconstruction in this patient cohort.